Optimal Control Policy for State Dependent Queueing Model with Service Interruption, Setup and Vacations - Jain, Madhu; Chauhan, Deepa (Journal of Informatics and Mathematical Sciences, 2010)
Present investigation deals with optimal management policy for Markovian queue with server breakdowns, vacations and setup. The customers arrive in Poisson fashion to get the service. The server may breakdown during the service and goes for repair immediately. By applying probability generating function technique queue length distribution is obtain for different states of the server. Further we determine the probability of empty system, expected number of units in the system, total expected cost function etc. Cost analysis has also been done. To validate analytic results, numerical experiment has been performed.